Peningkatan Kapasitas Petani melalui Pelatihan dan Demplot Padi Inpago Unram I untuk Ketahanan Pangan di Desa Suranadi Kabupaten Lombok Barat - Suliartini, Ni Wayan Sri; Aryana, I Gusti Putu Muiarta; Sukartono, Sukartono; Susilawati, Dwi (Universitas Mataram, 2024)
Superior varieties of Inpago Unram I along with cultivation technology and empowering farmer groups in rural areas are needed in order to maintain national rice self-sufficiency. The problem encountered in Gapoktan Mata Air 2 Suranadi Village is that they are not yet familiar with the Inpago Unram I variety. The purpose of the activity is to increase participants' knowledge and skills about Inpago Unram I rice cultivation applications. The method used is the training method followed by practical work in the field and participatory action research in the field from preparation to harvest. The stages of the activity include counseling and field laboratory practice (Demplot) on 4:1 legowo planting, use of optimum seedling age on a land area of 10 ares. Evaluation to measure the success of this activity is carried out through pre-tests and post-tests of participants and participant responses to the implementation of field practice. The training activity began with the delivery of material by the community service team about Inpago Unram I Red Rice as Functional Rice and the application of its cultivation technology, which was continued with discussion. During the counseling activity, participants were actively involved. This was shown by various questions asked by participants during the discussion. The activity was continued with practical work in the field from preparation to harvest. Based on the results of the activity, it was concluded that there was an increase in the capacity of training participants through increased knowledge and skills of participants about Padi Inpago Unram I as a functional rice quality seed based on the results of the pre-test and post-test, namely from 58.5% to 88.5% and the activeness of participants during the extension. The increase in the skills of training participants was shown by the active involvement of participants in the demonstration plot by practicing rice cultivation techniques with the 4:1 legowo row system at a seedling age of 18 days.